2019
DOI: 10.1007/s11104-019-04210-x
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Fungi participate in driving home-field advantage of litter decomposition in a subtropical forest

Abstract: The original version of this article unfortunately contained a mistake. The labels of y-axes in Fig. 2 should presented unitless. Fig 2. has now been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The hypothesis is that home-field advantage effects are driven by species-specific associations between plants and decomposer communities (Freschet et al, 2012a;Austin et al, 2014). Recent experimental work showed that different litter types can indeed harbor specific litter microbiomes (Keiser et al, 2011;Lin et al, 2019) and that variation in abundant litter fungal groups can contribute to home-field advantage effects (Veen et al, 2019). This results in plant-specific patterns in nutrient release (Perez et al, 2013) and, hence, may contribute to littermediated PSFs.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis is that home-field advantage effects are driven by species-specific associations between plants and decomposer communities (Freschet et al, 2012a;Austin et al, 2014). Recent experimental work showed that different litter types can indeed harbor specific litter microbiomes (Keiser et al, 2011;Lin et al, 2019) and that variation in abundant litter fungal groups can contribute to home-field advantage effects (Veen et al, 2019). This results in plant-specific patterns in nutrient release (Perez et al, 2013) and, hence, may contribute to littermediated PSFs.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
“…(3) Elucidate the species-specificity of litter-mediated PSF effects. Evidence is accumulating that plant litters build up unique decomposer communities (Lin et al, 2019;Veen et al, 2019), which may drive litter-mediated PSF via the biotic plant pathway. This may however generate relatively unspecific feedback effects, because different plant species may all profit from nutrients liberated from litter by specialized decomposer communities, however this is not tested.…”
Section: The Way Forwardmentioning
confidence: 99%